2021
DOI: 10.25156/ptj.v11n1y2021.pp38-41
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Gingival Health Status among Patients with Fixed Orthodontic Appliance

Abstract: Fixed orthodontic appliances corrupt plaque removal, proper oral hygiene, and gingival health so periodontal evaluation is important to be checked in every appointment. The aim of the present study was to assess gingival health among patients with a fixed orthodontic appliance. A clinical comparative study conducted on 25 patients with an aged ranged from 15 to 25 years. Clinical parameters included plaque index (PI), gingival index (GI), and bleeding on probing (BOP) were recorded at base line before starting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(12 reference statements)
1
0
0
Order By: Relevance
“…The New group showed a significant increase of the bleeding values after 4 weeks (p= 0.010). This result is in agreement with a study found that patients with fixed orthodontic appliances had significant increase in the mean value of bleeding on probing scores after 4 weeks [27], while other study showed this parameter increased at the initial stage of treatment (first month) but without statistically significant difference from baseline [28].…”
Section: Bleeding Scoressupporting
confidence: 92%
“…The New group showed a significant increase of the bleeding values after 4 weeks (p= 0.010). This result is in agreement with a study found that patients with fixed orthodontic appliances had significant increase in the mean value of bleeding on probing scores after 4 weeks [27], while other study showed this parameter increased at the initial stage of treatment (first month) but without statistically significant difference from baseline [28].…”
Section: Bleeding Scoressupporting
confidence: 92%